EFFECT OF USING TONGUE TWISTER ON STUDENTS’ VOWEL PRONUNCIATION SKILLS AT UNIVERSITAS MUHAMMADIYAH BULUKUMBA; INDONESIAN VILLAGE LEARNER CONTEXT - Sri Wahyuni Thamrin; Andi Anugrah M; Halijah Halijah; Haerul Mutiah (Universitas Muhammadiyah Makassar, 2023)
Pronunciation is one of the speaking elements that must be mastered by foreign learners. However, students still found difficulties when pronouncing English words. Therefore, tongue twister was thought to be one effective technique to help students articulate the English words. The research applied pre-experimental design with only one experiment class. The class consisted of 15 participants from English Education Departement Program of Universitas Muhammadiyah Bulukumba and was chosen through purposive sampling technique. Statistical technique was applied to confirm the hypotheisis. Based on the test of significance result, it was found out that t test value is higher than the t table value (2.0351.708). This indicates that students’ pronunciation skills improved after students learnt with tongue twister which was combined with some other methods. Furthermore, it is also informed that there were some kinds of pronunciation errors made and the dominant errors found is phonetic errors due to the effect of students’ native language systems.